Effects of injectable contraceptives on intraocular pressure among women of child bearing age - Uwagboe, Precious N.; Uwagboe, Charles U.; Mba, Chioma R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The presence of female sex hormones has been linked to variation in intraocular pressure. Numerous studies have revealed that these hormones exert neuroprotective effect and a vascular effect on intraocular pressure regulation. This study was to determine the effect of injectable contraceptives on intraocular pressure in women of child bearing age. Methods: It was a cross-sectional study, carried out at the University of Benin Teaching Hospital involving 85 healthy Nigerian women of child bearing age (20-50 years). The women were divided into two groups 20-35 years (Mean age was 29.66±3.43) and 36-50 years (Mean age 40.66±4.41). A brief case history was conducted to gain information on their personal data, oculo-visual history and general health. Intraocular pressure (IOP) was measured at baseline and two months after injectable contraceptive. Results: There was no statistical significant difference in the IOP reading at baseline and after injectable contraceptives among women in group 20-35 (p=0.819), whereas women in group 36-50 years showed a Statistical significant difference in their IOP at baseline and after injectable contraceptives (p=0.049). Conclusions: Injectable contraceptives have significant effect on IOP of healthy women of childbearing age. Further studies involving a larger sample should be conducted over a long duration in order to achieve a better generalization of the findings on this subject matter.